Online waqf acceptance in Malaysia / Mohamad Faisal Mohamed Yusof - Mohamed Yusof, Mohamad Faisal (2015)
The waqf is defined as an act of holding the certain property and preserving it for benefits of muslims community. There are several researched have been done on waqf however there are limited researches in understanding the factors that influence the online waqf acceptance. The past research usually focused on the cash waqf and management of waqf properties. The research is aiming in identifying the factors that influence the online waqf acceptance in Malaysia. The Technology Acceptance Model (TAM) and DeLone and McLean model is adapted in this study because the TAM is the most commonly used model in identifying the user acceptance in technology. A survey was conducted with IT professional that furthering their studies in Masters of Science in Information Technology, Faculty of Computer and Mathematical Science, UiTM Shah Alam. They are the potential group that will contribute to waqf. This research will produce the factors that influence the online waqf acceptance and proposed the conceptual model for online waqf environment. The findings from this research found that, perceive usefulness and information quality are the significant factors that influence the online waqf acceptance in Malaysia. In addition, the conceptual model has been constructed to improve the online waqf environment. The conceptual model from this research will contribute to organization that manages the waqf fund by providing the information about the factors that influence the online waqf acceptance in Malaysia.